Visual monitoring of the break surface of the installation connection of electronic equipment - Невлюдов, І. Ш.; Стародубцев, М. Г.; Демська, Н. П.; Омаров, Ш. А. (ХНУРЕ, 2019)
The progress of modern technology, expansion of the range of tasks assigned to the system control, high accuracy requirements, noise immunity, speed, etc. has led to increasing complexity of electronic technology and the creation of complex systems designed to solve a number of important tasks. In turn, the complexity of the instrument may lead to a sharp reduction in its reliability, which in some cases is dangerous, for example, when used in medicine, the military, while space research, transport, etc. To provide diagnostic functions and subsequently the functions of the prognostics of technical condition of electronic devices and their critical components (e.g., a flexible switch structures) it is necessary to create an effective tool for monitoring the status of the product. The aim of this study is to test the theoretical provisions on a diffuse scattered light surface tear by experimental studies of the spectrum of spatial frequencies of images of the surface of rupture. This paper proposes a method of obtaining images of the analyzed surface with its reflected light flux, providing the quantitative estimate of the amount of diffuse reflective sites, using the software. It is assumed that display physical and chemical processes, for their visual perception greatly enhance monitoring capabilities and will provide recommendations on the optimal scheme of optical control of surface gap, which will greatly reduce the complexity of control operations.